Automated and manual microscopic analyses for leukocyte differential counts in exudative pleural effusions: Real-world disagreement and clinical application. Issue 37 (16th September 2022) - Lee, Jaehee; Kim, Yu Kyung; Park, Ji Eun; Lee, Yong Hoon; Choi, Sun Ha; Seo, Hyewon; Yoo, Seung Soo; Lee, Shin Yup; Cha, Seung-Ick; Park, Jae Yong; Kim, Chang Ho
Abstract : Differential leukocyte counts of pleural fluid are routinely recommended for the early diagnosis and management of exudative pleural effusions. Rapid automated cellular analysis agrees strongly with standard manual microscopic counts and has become a reality in many clinical laboratories. However, discordant results sometimes observed between automated and manual analyses raise concern about using automated analysis to aid prompt differential diagnosis. This study aimed to evaluate the real-world disagreement between automated and manual leukocyte analyses in exudative pleural effusions and to investigate whether the discordant results occur in specific cellular ranges or randomly. We conducted a retrospective study of patients who were diagnosed with parapneumonic pleural effusions (PPE), tuberculous pleural effusions (TPE), and malignant pleural effusions (MPE) between September 2018 and December 2020. Differential and predominant leukocyte counts were performed using an automated XN-350 analyzer with a two-part differential count consisting of polymorphonuclear (PMN) and mononuclear (MN) leukocytes and a manual method with Wright-stained cytospin slides. We compared the two methods on cases of 109 PPEs, 50 TPEs, and 116 MPEs. Although the overall correlation between the two methods for differential leukocyte counts was excellent, there were etiologic variations; MPEs showed a lower correlation compared to PPEs and TPEs. Automated-PMN predominance almost corresponded to manual cytospin-neutrophilic predominance. In contrast, 10% of the automated-MN predominance did not correspond with the cytospin-lymphocytic predominance. These discrepancies occurred most in the automated-MN% range of 51% to 60%, followed by 61% to 70%. The PMN% range ≥50% and <30% on the automated analysis reliably corresponds to the neutrophilic and lymphocytic predominance, respectively. However, the MN% range of 51% to 70% may not coincide with lymphocytic predominance on manual cytospin analysis. This range leaves the potential cause of exudative pleural effusions open.